PENGARUH TINGKAT PENGETAHUAN DAN SIKAP BIDAN TENTANG INISIASI MENYUSU DINI (IMD) DENGAN PENERAPAN INISIASI MENYUSU DINI DI PUSKESMAS KOTA SURAKARTA - Ian Rossalia Pradita Puteri (Universitas Respati Yogyakarta, 2014)
Based On Data Survey Indonesia Well-Being Demography (SDKI) year 2007 Mention Baby Mortality Rate (AKB) stills very high that is 35 every 1.000 birth alive. one of [the] programe in course of depreciation acceleration execution Mention Baby Mortality Rate Initiation program gives early initiation. Follow watchfulness that done Dr. Karen Edmond year 2006, 22 % baby death preventable when is baby breastfed by the mother in one first clocks can birth. achievement 6 months asi exclusive base on Initiation program gives early initiation success in one first clocks. Aim from this watchfulness detects connection between erudition and midwife attitude about applications at Puskesmas City of Surakarta. Observasional analytic study with cross sectional approach. Population of 61 midwifes at public health center in Surakarta, the sampel by simple random sampling as many as 41 midwifes. The data collect with research instrument with questionnaire to measure knowledge, attitudes, and applications. Data analysis using logistics regression. data processing using SPSS program. Shows that a large part aged midwife 20-40 year as much as 24 midwifes (60%), midwife finished diploma III as much as 27 midwifes (68%), midwife works more than 5 year at puskesmas concerned as much as 28 person (70%), has tall erudition hits early initation as much as 33 midwifes (83%) as much as 23 midwifes (58%) has positive attitude or support towards applications early Initiation, and application early initiation well as much as 24 midwifes (60%). and from hypothesis test with regression logistic got or erudition 2,108 and or attitude 1,225, with confendence international 95% with limit erudition under 1,189 limits on 3,737, while for limit attitude under 1,050 and limit under 1,430, values n observation 40, values -2 logarithms likehood 32,356 and value negelkerker r2 with value 56,2%, with standard signifikansi for erudition 0,005<0,05 and for attitude 0,016<0,05 so there erudition level connection and midwife attitude about early initiation with applications early initiation.Keyword : Knowlagde, Attitude, Applications, Early Initiation